(3TQM cJGH SjHhjgs - (3GdMSf Hf YHO Gddg Hf GdeQRHGf GdSjQGaj GdfMhj , CHh SYjO, J (B368 (3g` s; (3SjHhjg , YeQh Hf YKeGf Hf bfHQ GdMGQKj, SjHhjg,J (B180 (3g` s
(3BNQgG (B:s
(3jfJgi HCKfGA GdcdGe Ydi GdUaI GdeTHgI s
(3GdChQGb ef (B1-40 (3cJHJ HNW MOjKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B10s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B17 - (3U (B387 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1427s
(3eUOQ GbJfGA GdCUd (B:s
(3Sdje CZG (B(1158) s
Keywords: (3GdfMhs